Diagnosis of neonatal and adult sepsis using a Serum Amyloid A lateral flow test - Julia Nowak; Jacquellyn Nambi Ssanyu; Flavia Namiiro; Nicola Mountford; Avery Parducci; Katarina Domijan; Mandy Daly; Deirdre O’Brien; Eithne Barden; Kieran Walshe; Sean Doyle; Peter Waiswa (PLoS ONE, 2025)
Sepsis is the overwhelming immunological response to infection, which if not treated can lead to multi-organ failure, shock and death. Specifically, neonatal sepsis results in 225,000 neonatal deaths globally per annum. Moreover, Uganda experiences one of the highest materno-fetal death rates (62,000 p.a.), with neonatal sepsis deaths at approximately 6,500 p.a.. The difficulty in diagnosing neonatal sepsis lies in the non-specific signs and symptoms associated with sepsis and an absence of definitive sepsis-specific biomarkers. However, serum amyloid A (SAA) detection has potential as a superior biomarker for the diagnosis of probable neonatal sepsis. Herein, in ethically-approved studies we have deployed a competitive lateral flow test (NeoSep-SAA (research-use only)) to detect SAA in whole blood at patient bedside in a resource-limited environment. Results are available within 10 minutes and test format is compatible with small blood volumes available from neonates (5 μl). NeoSep-SAA exhibited a high sensitivity and specificity for diagnosis of adult sepsis, and in neonates showed a sensitivity and specificity of 92% (89%, 95%) and 73% (68%, 77%) with PPV and NPV of 78% (75%, 81%) and 90% (86%, 93%), respectively (n = 714 individuals; 95% CI). NeoSep-SAA showed superior sensitivity for neonatal sepsis over C-Reactive Protein detection (sensitivity: 37%), albeit with some sacrifice of specificity. NeoSep-SAA enabled rapid diagnosis, which combined with minimally-invasive blood withdrawal, was less stressful for neonates. Overall, NeoSep-SAA can readily identify infection/inflammation and has the potential to enable rapid and informed clinical decisions to combat sepsis. This approach has potential to improve neonatal sepsis detection and reduce neonatal mortality in line with United Nations Sustainable Development Goal (SDG) 3.2 objectives.